2021
DOI: 10.1007/s00401-021-02314-2
|View full text |Cite
|
Sign up to set email alerts
|

The olfactory nerve is not a likely route to brain infection in COVID-19: a critical review of data from humans and animal models

Abstract: One of the most frequent symptoms of COVID-19 is the loss of smell and taste. Based on the lack of expression of the virus entry proteins in olfactory receptor neurons, it was originally assumed that the new coronavirus (severe acute respiratory syndrome coronavirus 2, SARS-CoV-2) does not infect olfactory neurons. Recent studies have reported otherwise, opening the possibility that the virus can directly infect the brain by traveling along the olfactory nerve. Multiple animal models have been employed to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 132 publications
(322 reference statements)
4
112
0
2
Order By: Relevance
“…On the other hand, analysis of cerebral spinal fluid samples and post-mortem brain tissues has provided inconsistent evidence for the neuroinvasion of COVID-19 [42]. When reviewing findings from animal models, Butowt et al [43] concluded that the evidence for the olfactory route to brain infection is weak, and that the loss of smell does not indicate that the virus has entered the brain. In short, the mechanisms behind the neurological symptoms in COVID-19 infection and the potential for neuroinvasion of the virus in humans is still not clear [44].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, analysis of cerebral spinal fluid samples and post-mortem brain tissues has provided inconsistent evidence for the neuroinvasion of COVID-19 [42]. When reviewing findings from animal models, Butowt et al [43] concluded that the evidence for the olfactory route to brain infection is weak, and that the loss of smell does not indicate that the virus has entered the brain. In short, the mechanisms behind the neurological symptoms in COVID-19 infection and the potential for neuroinvasion of the virus in humans is still not clear [44].…”
Section: Discussionmentioning
confidence: 99%
“…Many previous reports have suggested that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) gains access to the brain by using an olfactory route from the nose to the brain ( Bougakov et al, 2020 ; Briguglio et al, 2020 ; Butowt and Bilinska, 2020 ; Li et al, 2020 ; Natoli et al, 2020 ; Zubair et al, 2020 ; Burks et al, 2021 ; Meinhardt et al, 2021 ), similar to some other neuro-invasive viruses that are known to infect olfactory receptor neurons and spread from these first-order olfactory neurons to secondary and tertiary olfactory targets in the brain ( Barnett and Perlman, 1993 ; van Riel et al, 2015 ; Dubé et al, 2018 ). Indeed, it has been shown that SARS-CoV-2 can accumulate in various brain regions, in animal models (reviewed in: Butowt and von Bartheld, 2020 ; Rathnasinghe et al, 2020 ; Butowt et al, 2021 ) and in a small number of human patients with COVID-19 ( Ellul et al, 2020 ; Matschke et al, 2020 ; Meinhardt et al, 2021 ; Mukerji and Solomon, 2021 ; Solomon, 2021 ; Thakur et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the route along the olfactory nerve from the nose to the brain is controversial for SARS-CoV-2, primarily for two reasons: (1) the olfactory receptor neurons do not express the obligatory virus entry receptor, angiotensin-converting enzyme 2 (ACE2), or expression is restricted to a very small subset of these neurons ( Butowt and von Bartheld, 2020 ; Cooper et al, 2020 ; Brechbühl et al, 2021 ; Butowt et al, 2021 ). Because sustentacular cells tightly enwrap olfactory receptor neurons ( Liang, 2020 ), these ACE2-expressing support cells can easily be mistaken for olfactory receptor neurons, resulting in false positive identification.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations